Pengaruh Penggunaan Tepung Protein Kedelai Sebagai Pengikat Teradap Organoleptik, Total Plate Count dan Oksidasi Lemak Pada Sosis Sapi Ongol - Fangidae, Fransiska Eulalia Cristin; Noach, Yakob Robert; Sulmiyati (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of the exploration was to find the organoleptic quality, microbiological quality and fat oxidation of Ongole beef sausage using soy protein flour as an additional ingredient. The study used a completely randomized design (CRD) with five treatments and three replications consisting of PO = 0% soy protein with 20% tapioca flour. P1= 5% soy protein flour with 15% tapioca flour. P2 = 10% tapioca flour, 10% soy flour, P3 = 5% tapioca flour, 15% soy flour, P4 = 0% tapioca flour, 20% soy flour. The parameters observed were organoleptic quality, TPC and fat oxidation. The results of analysis of variance show a significant mean (P<0.01) for TPC. However, it is not significant for organoleptic quality (color, taste, aroma and texture) and fat oxidation value. Treatment of soy protein flour with different levels was able to produce favorable values for the same organoleptic parameters. Treatment of soy protein flour combined with tapioca flour (P2 and P3) was able to reduce the TBA value.